2007
DOI: 10.1016/j.nuclphysb.2006.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional deconfinement in gauge theory

Abstract: The Z Z(N) center symmetry plays an important role in the deconfinement phase transition of SU(N) Yang-Mills theory at finite temperature. The exceptional group G(2) is the smallest simply connected gauge group with a trivial center. Hence, there is no symmetry reason why the lowand high-temperature regimes in G(2) Yang-Mills theory should be separated by a phase transition. Still, we present numerical evidence for the presence of a first order deconfinement phase transition at finite temperature. Via the Higg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
142
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(170 citation statements)
references
References 57 publications
25
142
0
Order By: Relevance
“…First we confirmed the proposed and earlier seen [6,16] first order transition for pure G 2 -gluodynamics which corresponds to the line κ = 0 in the phase diagram of the Higgs model. A first analysis on smaller lattices indicated that this first order transition is connected to the first order deconfinement transition in SU (3)-gluodynamics, corresponding to the limit κ → ∞, by a smooth curve of first order transitions.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…First we confirmed the proposed and earlier seen [6,16] first order transition for pure G 2 -gluodynamics which corresponds to the line κ = 0 in the phase diagram of the Higgs model. A first analysis on smaller lattices indicated that this first order transition is connected to the first order deconfinement transition in SU (3)-gluodynamics, corresponding to the limit κ → ∞, by a smooth curve of first order transitions.…”
Section: Discussionsupporting
confidence: 87%
“…The smallest simple and simply connected Lie group with a trivial center is the 14 dimensional exceptional Lie group G 2 . This is one reason why G 2 gauge theory with and without Higgsfields has been investigated in series of papers [6][7][8][9][10][11]. Although there is no symmetry * bjoern.wellegehausen@uni-jena.de, wipf@tpi.uni-jena.de and Christian.Wozar@uni-jena.de reason for a deconfinement phase transition in G 2 gluodynamics it has been conjectured that a first order deconfinement transition without order parameter exists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is probably surprising is that the results of these analysis gave a picture much similar to that of standard SU(N ) theory: the spectrum of the G 2 theory at zero temperature is composed only of color neutral objects [11,12,15], the string tension at intermediate distances (i.e. before string breaking [20]) satisfies Casimir scaling [13,18,20], a first order deconfinement transition is present [14,16,22], (quenched) chiral symmetry is broken in the low temperature phase and restored above the critical temperature [19], the topological susceptibility is suppressed above deconfinement [21], propagators [17] and thermodynamical observables (like e.g. pressure and trace anomaly) [22] do not show any qualitative difference with respect to the SU(N ) case.…”
Section: Jhep03(2015)006mentioning
confidence: 98%
“…Bearing all this in mind, it is not surprising that the G 2 lattice gauge theory was actively investigated in the past, both at zero and finite temperature [11][12][13][14][15][16][17][18][19][20][21][22]. What is probably surprising is that the results of these analysis gave a picture much similar to that of standard SU(N ) theory: the spectrum of the G 2 theory at zero temperature is composed only of color neutral objects [11,12,15], the string tension at intermediate distances (i.e.…”
Section: Jhep03(2015)006mentioning
confidence: 99%